The Effect of Nutrition Education Using Quiz Application Games (APKIS) on Knowledge and Consumption of Snacks in Adolescents - Eltri Yani Sunengsih; Yanuarti Petrika; Desi Desi; Maretalinia Maretalinia (Borneo Scientific Publishing, 2023)
Adolescents experience rapid growth and development and are a critical period for changes in health-related behaviours such as food choices and physical activity. The prevalence of obesity increased from 1.4% in 2016 to 7.3% in 2017. Nutrition education will be effective if supported by the right media and delivery methods, one of which is android-based media as a tool for nutrition education in children. The advantage of nutrition education with quiz game media is its ability to convey information and increase adolescent knowledge through interesting media. This study aims to determine the effect of nutrition education through quiz game application media (APKIS) on knowledge and consumption of adolescent snacks at MTs Negeri 2 Pontianak. This research is a quasi-experiment with a one group pretest and posttest design, conducted on 22 June-1 July 2022. A sample of 39 respondents was taken by simple random sampling. Variables of knowledge and consumption of snacks were analysed using paired t-test. The results showed a significant effect on knowledge before and after nutrition education (p-value 0.00 < 0.05), and there was an effect on the consumption of snacks before and after education (p-value 0.00 < 0.05). In conclusion, the use of quiz application game media (APKIS) has an effect on increasing knowledge and changes in snack food consumption.